Caracterização química do óleo essencial e atividades biológicas do extrato hexânco do cipó de Philodendron solimoesence A.C. Smith (ARACEAE) - Bacchus, Nakita Eugene (2016)
This study aimed to characterize the essential oil chemical composition of the vine of Philodendron solimoesens, native to mountain area of the municipality in São João da Baliza, Roraima State. Philodendron solimoesense belongs to the Araceae family, which according to popular medicine has anti-inflammatory and anti-venom serum activity. The essential oil of Philodendron solimoesense was extracted from fresh and dried vine by hydrodistillation in Clevenger type apparatus in different stationary period during three consecutive hours. The essential oil yold (w / n), obtained was 0.046% for the fresh sample and 0.030% for dry sample both in the dry season, the rainy season were 0.013% for the fresh sample and the dryone not observed yield. The chemical constituents was characterized by comparison of the mass spectra of the substances with the database of the gas chromatography mass spectrometry (GC-MS) system and Kovats index. It was identified 45 constituents for the essential oil extracted from fresh vine to dry season and 38 for dry vine in the same period, the highlights are respectively the (-)-β-caryophyllene with 12,09% and D-cadinene 17 83%. It also performed the verification of antioxidant potential by capturing the free radical DPPH (2,2-diphenyl-1-picrilhidrazila). The result obtained for the crude hexane extract of Philodendron solimoesense showed antioxidant potential. It was performed the toxicity test using Artemia salina microcrustacean, the results showed that the crude hexane extract of Philodendron solimoesense was not toxicity to Artemia salina. In the antifungal test the crude hexane extract of Philodendron solimoesense did not inhibit mycelial growth of the pathogen anthracnose, caused by the fungus of Colletotrichum gloeosporioides genus.